P04.03.B Rapid DNA methylation-based classification of pediatric brain tumors from ultrasonic aspirate specimens. (5th September 2022) - Simon, M; Kuschel, L P; von Hoff, K; Hernáiz Driever, P; Hain, E G; Koch, A; Capper, D; Schulz, M; Thomale, U; Euskirchen, P
Abstract: Background: Cavitating ultrasonic aspirator (CUSA) devices are commonly used in neurosurgical procedures to carefully debulk tumor from adjacent healthy brain tissue. Here, we explore the feasibility of using ultrasonic minced tumor tissue to classify otherwise discarded sample material by DNA methylation according to the respective World Health Organization (WHO) Classification of Tumors of the Central Nervous System (CNS) using low pass nanopore whole genome sequencing. Material and Methods: 21 ultrasonic aspirated specimens from patients undergoing surgery in the department of pediatric neurosurgery at the Charité-Universitätsmedizin Berlin with either newly diagnosed cerebral lesions or pre-treated lesions were processed by nanopore sequencing to generate copy number profiles and ad-hoc random forest classification. Results were compared to microarray-based routine profiling. Tumor purity was assessed. Results: In 19/21 (90.5 %) samples the minimum amount of 1, 000 CpG sites were sequenced. In 20/21 (95.2 %) cases copy number variation profiles could be generated and matched microarray derived copy number profiles, allowing for identification of diagnostically or therapeutically relevant pathognomonic alterations. 12/17 (70.6 %) samples were concordantly classified to the corresponding microarray-based diagnosis by routine neuropathological workup. Applying recently defined thresholds for nanopore-based classification resulted in sensitivity of 64.7 % and specificity of 100 %. Conclusion: CUSA referred sample material of pediatric brain tumors allows for methylation-based classification according to the respective WHO classification of CNS tumors with acceptable sensitivity and high specificity. Hereby, a promising opportunity for accurate classification of pediatric brain tumors by a time- and cost-efficient advanced molecular technique is offered using otherwise discarded tumor tissue.